Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Mind Mapping - Monalisa Maseru (Universitas Negeri Makassar, 2024)
This study aims to improve science learning outcomes by applying the mind mapping learning model. The subjects of this study were 25 students of class V SDN 2 Rantepao consisting of 11 girls and 14 boys. The study consisted of two cycles, each cycle consisting of two meetings with the time allocation for each meeting being 2 x 35 minutes. Data collection techniques using observation, interviews, and tests. Observation guidelines are used every time learning takes place, tests are used every cycle ends at every second meeting ends. The interview guide was used at the end of the cycle. Based on the results of the research, it shows that there is an increase in student learning outcomes through the application of the mind mapping model. The application of the mind mapping learning model in science learning in cycle I with a classical percentage value of 36% and in cycle II achieved a classical percentage value of 92%. The conclusion from the results of this study is that by using the mind mapping learning model on science material can improve student learning outcomes at SDN 2 Rantepao.